Code-Switching Between Romanized Bangla and English: A Sociolinguistic Study of Social Media Posts - M M Fahim Shahriar (International Journal of Education, Language, and Religion, 2026)
The Bangla language has a core national identity due to the fierce resistance of the 1952 language movement. Over time, a hybrid linguistic space has been created on social media for various factors. This sociolinguistic study explores the implementation of code-switching between Bangla text written in the Latin script known as Romanized Bangla and English in Bangladeshi social media, examining social and technical factors and structural patterns in online interactions. A descriptive quantitative analysis of social media posts and literature on code-switching, romanization, and digital communication in the Bangladeshi context was conducted to identify overarching themes. The primary data collected from social media postings were obtained from dominant platforms such as Facebook, Instagram, and WhatsApp, as per interaction between multilingual speakers. Our findings demonstrate that the intermixing of Bangla and English in a sentence or a clause is a widely prevailing pattern (e.g., "ami eto tried chilam j, I had to take a bus"). The unconscious usage of mixed code during their conversation is noticeable, which may affect the user's ability to use the language in its pure form. The analysis revealed the dominant pattern driven by technological compatibility and also how it is potentially declining formal Bangla writing proficiency. It is not an indication of linguistic deficiency but rather an expression of a dynamic, bilingual identity.